2009
DOI: 10.1016/j.neulet.2009.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II inhibits GABAergic synaptic transmission in dorsolateral periaqueductal gray neurons

Abstract: The purpose of this study was to determine the role of angiotensin II (Ang II) in modulating inhibitory and excitatory synaptic inputs to the dorsolateral periaqueductal gray (dl-PAG). The whole cell voltage-clamp recording was performed to examine inhibitory and excitatory postsynaptic currents (IPSCs and EPSCs) of the dl-PAG neurons. Ang II, at the concentration of 2 µM, decreased the frequency of miniature IPSCs from 0.83 ± 0.02 to 0.45 ± 0.03 Hz (P < 0.05) in 10 tested neurons. This did not significantly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…102 Pharmacological research has demonstrated that the RAS components are localized on the opioid-rich brain areas, including the PAG and trigeminal nucleus of the spinal cord. [103][104][105] Furthermore, AngII has been shown to induce the release of β-endorphins in the brain. [106][107][108] Therefore, it may be possible that peripheral AngII may increase the release of endogenous opioids from the sympathetic ganglia or facilitate the effectiveness of the endogenous opioid system to produce analgesic actions.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…102 Pharmacological research has demonstrated that the RAS components are localized on the opioid-rich brain areas, including the PAG and trigeminal nucleus of the spinal cord. [103][104][105] Furthermore, AngII has been shown to induce the release of β-endorphins in the brain. [106][107][108] Therefore, it may be possible that peripheral AngII may increase the release of endogenous opioids from the sympathetic ganglia or facilitate the effectiveness of the endogenous opioid system to produce analgesic actions.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…administration of Ang (1-7) promoted anxiolytic-like effects reflected by the increased percentage of time spent and frequency of entries in the open arms of the EPM, as well as increased head-dipping behavior in the open arms and decreased stretching [43]. Considering specifically the PAG, which is one of the key brain regions involved in mediating anxiety, Ang (1-7) injected into the PAG inhibits its neuronal activity via Mas receptor and this effect is opposed to Ang II in the central nervous system [42,71]. Thus, Ang (1-7) appears to counterbalance most of the Ang II effects [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, renin substrate, Angs I, II and III modulate nociception in the vlPAG [40]. These and other evidence suggest that the RAS is engaged in the regulation of the functional activity of the PAG [41,42]. More interestingly, vlPAG can synthesize short chain peptides such as Ang (1-7) and Ang (5)(6)(7)(8) from Ang II and Ang III [8,40].…”
Section: Introductionmentioning
confidence: 85%
“…5 It inhibits GABAergic synaptic transmission in dorsolateral periaqueductal gray neurons through activation of presynaptic AT1 receptors. 6 Hence, ACE inhibitors and AT1 receptor antagonists can facilitate GABAergic transmission which is useful in seizure prevention.…”
Section: Introductionmentioning
confidence: 99%